2016
DOI: 10.1123/jpah.2015-0436
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in People With Posttraumatic Stress Disorder: A Systematic Review of Correlates

Abstract: Hyperarousal symptoms are associated with lower physical activity participation among people with PTSD and should be considered in the design and delivery of individualized exercise programs targeting this population. The role of social, environmental, and policy factors on physical activity participation among people with PTSD is unknown and should be addressed by future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 51 publications
(78 reference statements)
1
37
3
Order By: Relevance
“…For example, individuals with PTSD may be less likely to exercise given a heightened concern for safety, which is common in PTSD, 35 or fear of trauma-relevant bodily arousal symptoms triggered by exercise, such as shortness of breath, increased heart rate, and perspiration. 36 This possibility is supported by recent evidence that PTSD hyperarousal symptoms (as opposed to re-experiencing or avoidance symptoms) show a particularly robust inverse relationship with exercise. 3537 Additionally, PTSD symptoms may undermine motivation to engage in PA and make it more difficult to start and maintain an exercise program.…”
Section: Discussionmentioning
confidence: 85%
“…For example, individuals with PTSD may be less likely to exercise given a heightened concern for safety, which is common in PTSD, 35 or fear of trauma-relevant bodily arousal symptoms triggered by exercise, such as shortness of breath, increased heart rate, and perspiration. 36 This possibility is supported by recent evidence that PTSD hyperarousal symptoms (as opposed to re-experiencing or avoidance symptoms) show a particularly robust inverse relationship with exercise. 3537 Additionally, PTSD symptoms may undermine motivation to engage in PA and make it more difficult to start and maintain an exercise program.…”
Section: Discussionmentioning
confidence: 85%
“…However, we did not specifically examine other mechanisms linking PTSD to functional performance. A number of possible mediators exist, including, for example, changing levels of physical activity (Vancampfort et al., ), pain and comorbid anxiety disorders including PTSD (Asmundson, Coons, Taylor, & Katz, ; Asmundson & Katz, ), or increased fatigue or fatigability that may co‐occur with PTSD (Keller‐Ross, Schlinder‐Delap, Doyel, Larson, & Hunter, ), potentially signifying targets for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials have demonstrated that exercise, the structured and planned form of PA, has anxiolytic effects in people with and without anxiety disorders (Herring, Lindheimer, & O'Connor, ; Herring, O'Connor, & Dishman, ; Stubbs, Vancampfort et al, , ). Previous reviews have also demonstrated that a single bout of exercise can help alleviate anxiety symptoms in people with anxiety disorders (Strohle, Ströhle, Graetz, & Scheel, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially due to shared etiological biological factors between anxiety and cardiovascular disorders (e.g., increased inflammation and oxidative stress; Belem da Silva et al, 2017), but also due to modifiable risk behaviors like lower physical activity (PA) levels and increased sedentary behavior (Stubbs, Koyanagi et al, 2017;Vancampfort, Stubbs, Herring, Hallgren, & Koyanagi, 2018). Although several previous cross-sectional studies suggest that people with anxiety disorders or higher levels of anxiety symptoms are more likely to engage in lower levels of PA (22.9% versus 16.6%; Dillon, McMahon, O'Regan, & Perry, 2018;Stubbs, Koyanagi et al, 2017) and spend more time in sedentary activities when compared with people without anxiety (Dillon et al, 2018;Teychenne, Costigan, & Parker, 2015;Vancampfort et al, 2016Vancampfort et al, , 2018, PA is not always inversely associated with anxiety symptoms (Nguyen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%